Moving Interfaces in Crystalline Solids - Fischer, Franz D.; Schmid, Erich; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2005)
Moving Interfaces in Solids are typically phase boundaries and grain or subgrain boundaries. Continuum thermodynamics and continuum mechanics are applied to explain the motion process. Related numerical and experimental concepts are dealt with. Experts from material physics and mechanics bridge the gap between these fields. The reader is offered a common view of interface mtion in a unique representation. Examples are presented for various material systems.
Application of Configurational Mechanics to Elastic Solids with Defects and Cracks -- Phase Separation in Binary Alloys - Modeling Approaches -- Utilization of the thermodynamic extremal principle for modelling in material science -- Thermodynamics and Kinetics of Phase and Twin Boundaries -- Moving Grain Boundaries During Hot Deformation of Metals: Dynamic Recrystallization.
Keywords: Mechanics; Mechanics, Applied; Solid Mechanics